2019
DOI: 10.3892/ijmm.2019.4409
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LAMTOR1 in pancreatic β‑cells increases glucose‑stimulated insulin secretion in mice

Abstract: Insulin secretion from pancreatic β-cells regulates glucose metabolism and is related to various diseases including diabetes. The late endosomal/lysosomal adaptor MAPK and mTOR activator 1 (LAMTOR1) is one of the subunits of the 'Ragulator' complex and plays an important role in energy metabolism including glucose metabolism. The present study was designed to explore the role of LAMTOR1 in murine pancreatic β-cell function. A murine model with β cell-specific deficiency (βLamtor1-KO) was generated to assess β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…LAMTOR1, a late endosomal/lysosomal connector, which acts as a MAPK and MTOR activator 1, plays important roles in energy and glucose metabolism. Huang et al [ 52 ] found that mouse models with β-cell LAMTOR1 gene-specific defects have higher glucose tolerance and glucose-stimulated insulin secretion during hyperglycaemic clamp and islet perfusion than control models. LAMTOR1 loss increases the amplification pathway induced by glutamic acid and acetyl-CoA carboxylase 1, ultimately leading to increased insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…LAMTOR1, a late endosomal/lysosomal connector, which acts as a MAPK and MTOR activator 1, plays important roles in energy and glucose metabolism. Huang et al [ 52 ] found that mouse models with β-cell LAMTOR1 gene-specific defects have higher glucose tolerance and glucose-stimulated insulin secretion during hyperglycaemic clamp and islet perfusion than control models. LAMTOR1 loss increases the amplification pathway induced by glutamic acid and acetyl-CoA carboxylase 1, ultimately leading to increased insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies based on LAMTOR1 conditional knockout models, the role of LAMTOR1 in metabolism was rarely explored. Only one recent study reported that the β-cell-specific knockout of LAMTOR1 resulted in improved glucose tolerance and increased glucose-stimulated insulin secretion ( Huang et al, 2020 ). For the first time, this study explored the role of macrophage LAMTOR1 in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…71156, Affymetrix). The primer sequences (Table 1) and thermocycling conditions were previously reported in García‐Ruiz et al 35 and Huang et al, 36 respectively. Reactions were performed using the CFX96 Real‑time System (Bio‑Rad Laboratories, Inc).…”
Section: Methodsmentioning
confidence: 99%